Amphoteric chalcogen-bonding and halogen-bonding rotaxanes for anion or cation recognition - Tse, YC; Docker, A; Marques, I; Félix, V; Beer, PD (Nature Research, 2025)
The ever-increasing demand in the development of host molecules for the recognition of charged species is stimulated by their fundamental roles in numerous biological and environmental processes. Here, capitalizing on the inherent amphoteric nature of anisotropically polarized tellurium or iodine atoms, we demonstrate a proof of concept in charged guest recognition, where the same neutral host structure binds both cations or anions solely through its chalcogen or halogen donor atoms. Through extensive 1H nuclear magnetic resonance titration experiments and computational density functional theory studies, a library of chalcogen-bonding (ChB) and halogen-bonding (XB) mechanically interlocked [2]rotaxane molecules, including seminal examples of all-ChB and mixed ChB/XB [2]rotaxanes, are shown to function as either Lewis-acidic or Lewis-basic multidentate hosts for selective halide anion and metal cation binding. Notably, the exploitation of the inherent amphoteric character of an atom for the strategic purpose of either cation or anion recognition constitutes the inception of a previously unexplored area of supramolecular host–guest chemistry.